2015
DOI: 10.1039/c5ta00256g
|View full text |Cite
|
Sign up to set email alerts
|

A stable metal–organic framework with suitable pore sizes and rich uncoordinated nitrogen atoms on the internal surface of micropores for highly efficient CO2 capture

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 72 publications
(109 reference statements)
1
41
0
Order By: Relevance
“…S6, †the low-pressure uptake for H 2 is completely reversible and the adsorption amount is 1.81 wt% (203 cm 3 g À1 ) and 1.34 wt% (150 cm 3 g À1 ) at 77 and 87 K under 1 bar respectively, which are quite comparable with highly porous MOFs under the same conditions. 43,44 Furthermore, the maximum adsorption amount of O 2 is 529 cm 3 g À1 at 77 K (Fig. S7 †), which is comparable to those of highly porous MOFs.…”
Section: Resultsmentioning
confidence: 56%
“…S6, †the low-pressure uptake for H 2 is completely reversible and the adsorption amount is 1.81 wt% (203 cm 3 g À1 ) and 1.34 wt% (150 cm 3 g À1 ) at 77 and 87 K under 1 bar respectively, which are quite comparable with highly porous MOFs under the same conditions. 43,44 Furthermore, the maximum adsorption amount of O 2 is 529 cm 3 g À1 at 77 K (Fig. S7 †), which is comparable to those of highly porous MOFs.…”
Section: Resultsmentioning
confidence: 56%
“…Examples of porous materials showing superior CO 2 uptake over CH 4 are reasonably common. 30 In many of these cases, workers have attributed the preferred CO 2 over CH 4 uptake to size exclusion mechanisms, 31 greater polarizability of CO 2 compared to CH 4 and preferred binding of CO 2 to pore surfaces 32,33 in addition to superior CO 2 adsorption kinetics. 34…”
Section: Gas Adsorption Studiesmentioning
confidence: 99%
“…Seth et al also reported a triazole‐containing cadmium MOF with accessible uncoordinated N atoms, exhibiting a similar CO 2 uptake (4.42 mmol g ‐1 ) at 1 bar and 273 K . Bao et al synthesized an air‐stable tetrazolate‐containing NENU‐520 with uncoordinated N atoms and suitable pore size (≈0.36 nm) for CO 2 adsorption . NENU‐520 exhibits a moderate CO 2 uptake (2.7 mmol g ‐1 ) at 1 bar and 298 K because of the limited surface area (387 m 2 g ‐1 BET), but extremely high IAST CO 2 /N 2 selectivity of up to 600 at 298 K, for a simulated gas mixture of 0.15 bar CO 2 and 0.85 bar N 2 .…”
Section: Co2 Capturementioning
confidence: 99%